JENIS DAN JUMLAH KONSUMSI TAMBELO, SIPUT DAN KERANG OLEH PENDUDUK DI KAWASAN MUARA MIMIKA, PAPUA - Hardinsyah Hardinsyah; Agus Sumule; John Letsoin (Food and Nutrition Society of Indonesia, 2006)
This study is intended to analyse type and amount of MSS (Mangrove worm, Snail and Shell) consumed by the local people live in 12 estuary villages of Mimika. About 30 people for each village - consist of children (2-10 yrs), teenages (11-19 yrs) and adults (>=20 yrs) from both sexes, were selected as subjects. The data collected include socio-economic ofthe family, type and amount of MSS consumption. The results showed that Bactronophorus thoracites (tambelo), Nerita balteata (snail) and Telecopium telescopium (snail), Naqueita capulina (snail) and Geloina sp (shell), Geloina cf coaxan (shell) were the six types of MSS commonly consumed by people in the study areas; and they were consumed by more than 10 % of the subjects with eating frequency more than three times a week for each. The mean intake of tambelo, snail and shell was 290.1±509.4, 96.0±271.2, and 152.8±278.6 g/week respectively in edible portion. Among the age groups, the highest intake of ambelo (433.2±627.5 g/week) and snail (133.8±387.9 g/week) was in adults, but the highest intake of shell (213.7±369.7 g/week) was in teenages. Intake data by village showed that, the highest intake of tambelo was in male of Mioko (542.1±730.8 g/week), the highest intake of snail was in female of Karaka (649.2±487.9 g/week), and so for shell (599.8±484.0 g/week). This implies that the MSS play important roles in the diet of the local people of Mimika’s estuary.